Konsep Wabi-Sabi Yang Diterapkan Dengan Teknik Sulam Dan Shibori Pada Busana Outerwear - Kania Gitaswari; Yulriawan Dafri; Esther Mayliana (Style : Journal of Fashion Design, 2021)
The creation of a work with the title "The concept of Wabi-Sabi applied with embroidery and shibori techniques in Outerwear Clothing" is the embodiment of individual ideas or thoughts to achieve inner satisfaction which is processed according to the abilities of the author. This work has character and aesthetic value, using balanced ideas, concepts, and techniques. The creation of the work uses the Japanese concept of wabi-sabi which is applied to outerwear inspired by kimono. Approach methods in the creation of works are aesthetic, ergonomic, and semiotic approaches. There are three creation methods used to search data according to the theme raised, namely data collection, data analysis, design, and embodiment. The technique of embodiment of the work applies shibori and embroidery techniques. The works resulting from this creation are four works of art, each of which has its own uniqueness and characteristics in terms of motifs, colors and pieces of clothing. It is hoped that in making this work useful for art connoisseurs and the community. And can contribute and creative discourse about culture and fashion.